FACTORS AND FEATURES OF THE SMART-ECONOMY DEVELOPMENT - Iryna Kalenyuk; Iryna Uninets (Izdevnieciba "Baltija Publishing", 2020)
The article examines the prerequisites and features of the SMART-economy. This new phenomenon is still insufficiently studied in the scientific literature. Different approaches and separate definitions of SMART-economy in the scientific literature are systematized. An understanding of SMART-economy in a narrow (as part of SMART-city) and broad sense (as a set of economic relations) is proposed. The main processes that determine the emergence of SMART-economy as an ecosystem are identified and disclosed. Digitalization (spread of ICT), institutionalization (penetration of ICT into public administration), urbanization (unprecedented growth of urban population and large cities), greening (increasing attention to environmental issues) and socialization (increasing the importance of solving social problems of the population) all contribute to the emergence of new quality of ecosystems. Based on the data, the trend of increasing the share of urban population in recent years is revealed, the data on the population of the largest cities in the world are given. The increasing in urban population highlights the problems of using ICT to solve the problems of greening, socialization, institutionalization in large cities.